2006
DOI: 10.1002/jor.20202
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of pyrosequencing molecular Gram stain, culture, and conventional Gram stain for diagnosing orthopaedic infections

Abstract: ABSTRACT:We have developed a combined real-time PCR and pyrosequencing assay that successfully differentiated the vast majority of gram-positive and gram-negative bacteria when bacterial isolates were tested. The purpose of this study was to evaluate this assay on clinical specimens obtained from orthopedic surgeries, and to prospectively compare the results of ''molecular Gram stain'' with culture and conventional direct Gram stain. Forty-five surgical specimens were obtained from patients who underwent ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…It is not yet known if the high prevalence of bacteria identified in those studies represents the cause of patients' infection or false-positive results. Our recent results 1 in which PCR was used to identify evidence of bacteria in apparently aseptically loose implants showed bacterial DNA in 12%, which is a smaller proportion to that of Tunney et al 5 or Mariani et al 6 However, in vitro studies have also shown that PCR can identify DNA from dead bacteria. 3 While the detection of dead bacteria is interesting, it carries less clinical importance than detecting viable bacteria.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…It is not yet known if the high prevalence of bacteria identified in those studies represents the cause of patients' infection or false-positive results. Our recent results 1 in which PCR was used to identify evidence of bacteria in apparently aseptically loose implants showed bacterial DNA in 12%, which is a smaller proportion to that of Tunney et al 5 or Mariani et al 6 However, in vitro studies have also shown that PCR can identify DNA from dead bacteria. 3 While the detection of dead bacteria is interesting, it carries less clinical importance than detecting viable bacteria.…”
mentioning
confidence: 65%
“…One hundred microliters of DNA extract was obtained for each sample. Quantitative PCR assays targeted 16S rDNA 1 and tuf using a Rotorgene 3000 1 (Corbett Research, Sydney, Australia). Tuf primer sequences (BioChem, Salt Lake City, UT) were: forward primer, 5 0 -ATGCCACAAACTCGTGA-3 0 , reverse primer, 5…”
Section: Pma Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five microliters of DNA extract was obtained for each sample. qPCR assays targeted 16S rDNA [5] and tufA DNA using a Rotorgene 3000 1 (Corbett Research, Sydney, Australia). The tufA primer sequences (BioChem, Salt Lake City, UT) were 5 0 -ATGCCACAAACTCGTGA-3 0 (forward primer) and 5 0 -ACCACGACCAGTGATTGAGAA-3 0 (reverse primer).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular methods, especially PCR, have been recognized as a sensitive tool for improving the diagnosis of prosthetic joint infections [5,15]. Mariani et al [7] suggested PCR may be more sensitive than conventional cultures and some cases of prosthetic joint infection may be misclassified as aseptic loosening using current culture methods.…”
Section: Introductionmentioning
confidence: 99%